Charlie Bone and the castle of mirrors [compact disc, unabridged] - Nimmo, Jenny (Nimmo, Jenny. Children of the red king (Audio), 2006)
Charlie and his magically gifted friends and relatives work together to rescue Billy Raven, a young orphan, from a mysterious and dangerous couple who have adopted him.